Continuous Application Of Modern Logical And Literary Materials In The Formation Of The Competence Of Students To Work With Akhbotrot (Global Scientific Review, 2025)
At the moment, the training of deeply and creatively thinking personnel in every possible way is an urgent topic, and it certainly begins with small elements. The methods and materials used in the elementary grades are no exception , and it is important that we teach the sources of the future that history knows, with a connection, zeroki, there is no future without history. And through this article , it is shown that in increasing the competence of students to work with information, not only materials that encourage today's creative thinking are great, but also the role of shields from ancestors.